2007
DOI: 10.1149/1.2756369
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochemical Activities of Pt–Ti Alloy PEFC Electrocatalysts

Abstract: Titanium is one of the most stable materials, remaining undissolved under strongly acidic polymer electrolyte fuel cell ͑PEFC͒ conditions. Nanocrystalline Pt-Ti alloy electrocatalysts with a catalyst grain size of several nanometers have been successfully prepared by the colloidal and sol-gel method, characterized by X-ray diffraction, field-emission scanning electron microscope, scanning transmission electron microscope, energy-dispersive X-ray analysis, and X-ray photoelectron spectroscopy. Electrochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…One way to achieve this is to reinforce the design of the catalyst by impregnating Pt particles with substances that increase their stability on the carbon support. Platinum-Titanium (Pt-Ti) and PlatinumRuthenium/Carbon (Pt-Ru), for example, were suggested by [202] as suitable alloys with high Pt stability under severe acidic conditions. When these alloys were utilised in the design of MEA, the cell was more CO-tolerant than pure Pt catalyst as deduced from the negative shift measurements of the cell potential.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to achieve this is to reinforce the design of the catalyst by impregnating Pt particles with substances that increase their stability on the carbon support. Platinum-Titanium (Pt-Ti) and PlatinumRuthenium/Carbon (Pt-Ru), for example, were suggested by [202] as suitable alloys with high Pt stability under severe acidic conditions. When these alloys were utilised in the design of MEA, the cell was more CO-tolerant than pure Pt catalyst as deduced from the negative shift measurements of the cell potential.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…Inaba et al [44] also suggested introducing an anti-gas crossover layer, a peroxide decomposition layer and Fe 2+ ion-trap layer into the MEA design in order to prevent oxygen crossover and consequent formation of hydrogen peroxide and catalytic combustion at the anode. In addition, as mentioned in section 3.2, the MEA stability can be enhanced by impregnating the catalyst layer with alloys such as titanium [202], cobalt [188,203], aluminium oxide [213], titanium dioxide [214], zirconium dioxide [215] and tin dioxide [216].…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…In an effort to improve catalyst activity and reduce the cost of the catalyst, many modified Pt-based catalysts have been synthesized for the fuel cells, such as Pt-Ti, Pt-Pd, Pt-Co, Pt-Cr, Pt-Mn, and Pt-Fe [4][5][6][7]. However, these modifications still require a relatively high Pt loading.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the electroactivity of pure Pt towards ORR, platinum was usually dispersed into nano-scale particles [7][8][9][10][11]. Bimetallic electrocatalysts containing Pt, like alloys of PtCo and PtCr [11][12][13][14], PtRu [15], carbon-supported alloys of AuPt [16], PtTi [17], and PtNi [11], have been fabricated and found to present efficient electroactivity for ORR. In addition, preparation of some non-platinum alloys and their electroactivity for the ORR have been reported, including PdCo [18,19], PdFe [20], PdAu [21], and Co-Ni [22].…”
Section: Introductionmentioning
confidence: 99%